2014
DOI: 10.1590/1678-6343
|View full text |Cite
|
Sign up to set email alerts
|

Tongue papillae morphology of brown-throated sloth Bradypus variegatus (SCHINZ, 1825)

Abstract: The Bradypus variegatus inhabits the forests of South America and feeds from leaves, branches and sprouts from different plants. Due to its diet and the lack of literature on the morphological aspect of Xenarthras, five Bradypus variegatus tongues from animals which died from natural causes were evaluated, and they came from Pará State Museum Emílio Goeldi and were donated to the Laboratory of Animal Morphological Research (LaPMA) from UFRA, for revealing the different types of papillae and epithelial-connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 21 publications
(36 reference statements)
3
4
1
3
Order By: Relevance
“…The axis of each circumvallate papillae is oriented obliquely to the main axis of the tongue in Cingulata, but not in Pilosa. By our observations of Myrmecophagidae and C. unicinctus and the data in the literature (Benetti et al, ; Cupa‐Caparo, ; Kubota et al, ; Martins et al, ), it is possible to conclude that the circumvallate papillae of armadillos and sloths present more taste buds when compared to anteaters, in agreement with the conclusion of Kubota et al () that the tongue in anteaters may be poorly developed for taste function.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The axis of each circumvallate papillae is oriented obliquely to the main axis of the tongue in Cingulata, but not in Pilosa. By our observations of Myrmecophagidae and C. unicinctus and the data in the literature (Benetti et al, ; Cupa‐Caparo, ; Kubota et al, ; Martins et al, ), it is possible to conclude that the circumvallate papillae of armadillos and sloths present more taste buds when compared to anteaters, in agreement with the conclusion of Kubota et al () that the tongue in anteaters may be poorly developed for taste function.…”
Section: Discussionsupporting
confidence: 91%
“…The presence of two circumvallate papillae is consistent among xenartrans (Rapp, ; Sonntag, ). Some studies (Mayer, ; Münch, ; Silva et al, ) reported from three to eight circumvallate papillae in xenarthrans, but our observations and literature review suggest that these reports are mistaken or refers to a rare condition, not observed in the majority of the studies about the tongue of Xenarthra (Benetti et al, ; Dingler, ; Martins et al, ; Morais & Watanabe, ; Rapp, ; Sonntag, ; Sonntag & Duncan, ). The axis of each circumvallate papillae is oriented obliquely to the main axis of the tongue in Cingulata, but not in Pilosa.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…A língua dos exemplares estudados assim como em outras espécies de mamíferos selvagens como Panthera pardus saxicolor (leopardo) (SADEGHINEZHAD et al, 2017), Panthera tigris altaica (tigre) (EMURA et al, 2004), Suricata suricatta, (suricato) (ERDOGAN et al, 2016) Cerdocyon thous (mão-pelada) Chrysocyon brachyurus (lobo-guará) (LIMA, 2015) apresentou as três regiões usuais deste órgão: raiz, corpo e ápice. Observou-se ainda a existência de um sulco mediano, que dividia o dorso em duas metades simétricas direita e esquerda, como em Cuniculus paca (paca) (BERALDO-MASSOLI et al, 2013), Nasua nasua (quati) (SOUZA et al, 2012), Bradypus torquatus (preguiça-comum) (MARTINS et al, 2014) e sagui-de-tufo-preto (BRANCO et al, 2012 (CORRÊA et al, 2012;LIMA, 2015) e Kerodon rupestris (mocó) (SANTOS et al, 2015) e Callithrix penicillata (sagui-de-tufo-preto), já as funções destas papilas estão relacionadas com percepções de caráter gustativo (DELMANN ; BROWN 2003).…”
Section: Resultsunclassified